A night in the cemetery : and other stories of crime & suspense - Chekhov, Anton Pavlovich, 1860-1904; Sekirin, Peter (2008)
The English-language debut of Anton Chekhov's first collection of mystery and suspense tales. Considered one of the greatest dramatists of all time, Anton Chekhov actually began his literary career as a crime and mystery writer. Scattered throughout periodicals and literary journals from 1880-1890, Peter Sekirin brings together these psychological suspense stories in a premier collection that provides a fresh look into Chekhov's literary heritage and his formative years as a writer
A night at the cemetery -- What you usually find in novels -- The Swedish match -- A night of horror -- Willow -- A thief -- The only way out -- An expensive dog -- Curved mirror -- A court case -- The brother : a slice of life -- A confession -- In the darkness of the night -- The intentional deception -- On the sea : a sailor's story -- Ivan the cabman -- Perpetual mobile -- Evildoer -- Death of an office worker -- 75 grand -- At the cemetery -- The conversation of a man with a dog -- The wallet -- A dead body -- Too much talking! -- Conversation of a drunken man with a sober devil -- Psychopaths -- Assignment -- Fire in the steppe : an evil night -- Ignoramus -- Task -- Dreams -- A crime : a double murder case -- Drama -- An ambulance -- Bad business -- Misfortune -- The man who wanted revenge -- Thieves -- Murder -- Criminal investigator -- The drama at the hunt
Keywords: Chekhov, Anton Pavlovich, -- 1860-1904 -- Translations into English; Short stories, Russian -- Translations into English; Suspense fiction; Short stories